Meningkatkan Kemampuan Berhitung Anak Usia 5-6 Tahun Tk Tunas Jaya Melalui Penggunaan Bahan Alam - Windy Gusri Maryani; Numalina Nurmalina; Lusi Marleni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study is motivated by the low ability to count in children aged 5-6 years in group B at Tunas Jaya Kindergarten, Balam Jaya Village, Tambang District, Kampar Regency. The purpose of this study was to improve counting skills with the use of natural media in group B children aged 5-6 years at Tunas Jaya Kindergarten, Balam Jaya Village. The research design used in this research is class action research (PTK). This research was carried out in 2 cycles, in each cycle there were 2 meetings, which consisted of the following activities: planning, implementation, observation, and reflection. The research was conducted from May 20 to May 30, 2024. The instruments used in this research are observation sheets and documentation. The population and sample in this study were children aged 5-6 years in group B, totaling 15 children, 8 boys and 7 girls. Data collection techniques were carried out by observation and documentation. The data analysis technique in this research is quantitative descriptive technique. The results showed that there was an increase in children's counting ability starting from cycle I 40%, when carried out in cycle II to 86.7%.It can be concluded that the use of natural media can improve counting skills in children aged 5-6 years in group B at Tunas Jaya Kindergarten, Balam Jaya Village is said to be successful by reaching 86.7% in the very well developed category.